2015
DOI: 10.4103/0019-509x.176698
|View full text |Cite
|
Sign up to set email alerts
|

Cystosarcoma phyllodes: Pathological enigma: A retrospective review of 162 cases

Abstract: WLE with negative margins should be the initial surgery for PT. The role of adjuvant radiotherapy and chemotherapy is uncertain. PT is pathological enigma. Till date, no factors can accurately predict the recurrence and outcome. PT is known for unpredictable behavior and high recurrence rates, hence long-term follow-up is advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
1
15
0
1
Order By: Relevance
“…5 It is important to inform the patient with PT about the recurrence and metastatic risk according to the histologic features of the tumour (even if, in some cases, the histological grade alone does not correctly predicts the biological aggressiveness of the tumour and the clinical prognosis). 7,8 After many classifications have been proposed, the 2003 WHO Phylloid tumour classification has been the most widely accepted and commonly used. Considering the poor relation between histologic grade and prognosis, several authors have tried to identify genetic or molecular markers (MED12 mutations, 3 DNA ploidy, 4 collagen type III ␣1, 9 others).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It is important to inform the patient with PT about the recurrence and metastatic risk according to the histologic features of the tumour (even if, in some cases, the histological grade alone does not correctly predicts the biological aggressiveness of the tumour and the clinical prognosis). 7,8 After many classifications have been proposed, the 2003 WHO Phylloid tumour classification has been the most widely accepted and commonly used. Considering the poor relation between histologic grade and prognosis, several authors have tried to identify genetic or molecular markers (MED12 mutations, 3 DNA ploidy, 4 collagen type III ␣1, 9 others).…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant treatment with chemotherapy, 8,14,15 radiotherapy 8,14 or hormonal therapy presently have no clear evidence of benefit and remain controversial. Given the rarity of PT, randomized controlled trials are unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The median margin width has not been reported in the literature. Though the incidence of positive/close margin varied from 5.9 to 66.7%, revision surgery was performed only in few [43] 49 (30) 50 ( Age at presentation has also been described as a predictive factor for LR, but the results are contradictory. In a review by Spitaleri et al, it has been shown that young age (<35 years) is a poor prognostic factor for all phyllodes-related events [25] 21 (44) 6 (28.6) [32] 19 (11) 11 (57.9) in both univariate and multivariate analyses.…”
Section: Histological Classificationmentioning
confidence: 95%
“…The median tumor size ranges from 5.2 to 10.8 cm in various studies, and these report 10 cm as the significant cutoff for LR. [8,25,31,39,43] Studies reporting tumor size <5 cm as the significant cutoff have median tumor size in the range of 3.0-6.1 cm. [24,27,31,37] The hazard ratio (HR) has not been reported in most of the studies except in the study by Asoglu et al, where authors have demonstrated tumor size to be an independent predictor of LR in multivariate analysis.…”
Section: Histological Classificationmentioning
confidence: 99%
“…Ainda não existem fatores clinicopatológicos que possam predizer a recorrência e mortalidade. 1 A paciente em questão, atualmente, se encontra em acompanhamento para evitar futuras recorrências, por se tratar de paciente jovem de mama densa, foi optado pelo acompanhamento com Ultrassonografia das mamas, que inicialmente foi prescrita ser realizada de 6 em 6 meses por 3 vezes consecutivas.…”
unclassified